The relationship between workplace incivility and psychological distress in Sabah - Syed Azizi Wafa Syed Khalid Wafa; Enja Anak Manie; Ramraini Ali Hassan (2016)
The main purpose of this study is to investigate the relationship between workplace incivility and psychological distress in Sabah. The moderating variable of this study was education level. The research design is quantitative in nature. The study populations are the working adults in private and government sectors in Kota Kinabalu, Sabah. The quantitative method (questionnaires) was applied to determine the findings of the questionnaire which involves the analysis of numerical data and provides precise results. A total of 240 working adults were surveyed for this study. This represented from both the government and private sector. A convenient sampling method was used for data collection. A total of 300 questionnaires were distributed to the respondents. From 300 questionnaires, only 240 questionnaires were usable. From the findings, most of the respondents said that workplace incivility has significant relationship with individual outcomes. This study also indicates that there are significant difference in workplace incivility between management and non-management employees. Interestingly this study also found that women perceived instances of uncivil workplace mistreatment more negatively than men. This study through its research and findings can help to provide the information related to workplace incivility in Sabah.